Bioengineering Technologies for Cardiac Regenerative Medicine - Chingale, Mira; Zhu, Dashuai; Cheng, Ke; Huang, Ke (Frontiers in Bioengineering and Biotechnology, 2021)
Cardiac regenerative medicine faces big challenges such as a lack of adult cardiac stem cells, low turn-over of mature cardiomyocytes, and difficulty in therapeutics delivery to the injured heart. The interaction between bioengineering and cardiac regenerative medicine offers innovative solutions to this field. Cell reprogramming technologies were applied in both direct and indirect routes to generate patient-specific cardiomyocytes. Various non-viral or viral vectors have been utilized for gene editing to intervene in the gene expression patterns during the cardiac remodeling process. Cell-derived protein factors, exosomes, and miRNAs were isolated and delivered through engineered particles to overcome the limitations of cell therapy. Protein decoration, antibody modification, and platelet membranes have been used for targeting and precision medicine. Cardiac patches have been designed by transfer therapeutics in vehicles for better retention and integration. Other technologies such as 3D printing and 3D culture technologies were utilized to create replaceable cardiac tissue. Here, we discussed recent advancements in bioengineering and biotechnologies for cardiac regenerative medicine.